The duty to be morally enhanced - Persson, I; Savulescu, J (Springer Verlag, 2017)
We have a duty to try to develop and apply safe and cost-effective means to increase the probability that we shall do what we morally ought to do. It is here argued that this includes biomedical means of moral enhancement, that is, pharmaceutical, neurological or genetic means of strengthening the central moral drives of altruism and a sense of justice. Such a strengthening of moral motivation is likely to be necessary today because common-sense morality having its evolutionary origin in small-scale societies with primitive technology will become much more demanding if it is revised to serve the needs of contemporary globalized societies with an advanced technology capable of affecting conditions of life world-wide for centuries to come.